2020
DOI: 10.1038/s41467-020-19555-6
|View full text |Cite
|
Sign up to set email alerts
|

MEKK2 mediates aberrant ERK activation in neurofibromatosis type I

Abstract: Neurofibromatosis type I (NF1) is characterized by prominent skeletal manifestations caused by NF1 loss. While inhibitors of the ERK activating kinases MEK1/2 are promising as a means to treat NF1, the broad blockade of the ERK pathway produced by this strategy is potentially associated with therapy limiting toxicities. Here, we have sought targets offering a more narrow inhibition of ERK activation downstream of NF1 loss in the skeleton, finding that MEKK2 is a novel component of a noncanonical ERK pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…[ 68 ] Recent findings additionally demonstrate that MEKK2 is a key mediator of the aberrant ERK activation occurring in osteoblasts downstream of loss of function of NF1, a GTPase-activating protein that negatively regulates RAS activation. [ 70 ] Despite MEKK2-deficient mice displaying severe osteopenia, either genetic or pharmacologic inhibition of MEKK2 prevented the constitutive ERK activation occurring in models of skeletal NF1 disease and overall ameliorated the NF1-associated skeletal phenotypes. This work, alongside several prior studies establishing the ERK MAPK pathway as one, though likely not the only, mediator of NF1-associated skeletal diseases,[ 23 , 24 , 71 ] argues that ERK MAPKs are not unconditionally pro-anabolic.…”
Section: Map3ks Activating the Erk Mapk Pathway In Osteoblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 68 ] Recent findings additionally demonstrate that MEKK2 is a key mediator of the aberrant ERK activation occurring in osteoblasts downstream of loss of function of NF1, a GTPase-activating protein that negatively regulates RAS activation. [ 70 ] Despite MEKK2-deficient mice displaying severe osteopenia, either genetic or pharmacologic inhibition of MEKK2 prevented the constitutive ERK activation occurring in models of skeletal NF1 disease and overall ameliorated the NF1-associated skeletal phenotypes. This work, alongside several prior studies establishing the ERK MAPK pathway as one, though likely not the only, mediator of NF1-associated skeletal diseases,[ 23 , 24 , 71 ] argues that ERK MAPKs are not unconditionally pro-anabolic.…”
Section: Map3ks Activating the Erk Mapk Pathway In Osteoblastsmentioning
confidence: 99%
“…[ 73 , 74 ] Patients with NF1 display skeletal abnormalities including craniofacial dysmorphogenesis, osteopenia/osteoporosis, short stature, and impaired fracture healing. [ 75 , 76 ] Similarly, conditional mouse models lacking NF1 in various skeletal lineage cells display characteristic features of the skeletal abnormalities of NF1 patients, including impaired bone structure and severe cortical bone porosity in Nf1 Prx1 ,[ 77 ] Nf1 Col ,[ 71 ] Nf1 Osx ,[ 78 ] and Nf1 Dmp1 ,[ 70 ] mice. To understand the pathogenesis of NF1 skeletal manifestations, several studies have investigated target pathways mediating the aberrant ERK effects of NF1 loss of function in skeletal lineage cells.…”
Section: Regulators Of the Erk Mapk Pathway In Osteoblastsmentioning
confidence: 99%
“…The MAPK pathway is mainly composed of three subfamily members, including extracellular signalregulated kinase (ERK)1/2, ERK5, c-Jun N-terminal kinase (JNK1/2/3) and P38 mitogen-activated protein kinase (P38α/β/γ/δ MAPK), which after cascade phosphorylation, are transmitted to the nucleus and regulate the expression of downstream transcription factors [40]. The MAPK pathway operates in a three-tiered cascade: MAP kinase kinase kinases (MAP3K), MAP kinase kinases (MAP2K), and MAPKs [41]. MAPKs are widely expressed in various forces-stimulated mechanosensory cells to regulate transcription, and therefore influence bone/cementum homeostasis [42].…”
Section: Mapk Signalingmentioning
confidence: 99%
“…It is a common tumor predisposition syndrome[ 2 , 6 , 7 ] with a complex pathogenesis. Various studies have reported differing incidence rates, but the frequency of the disease is 1/(2500-4000)[ 2 , 3 , 8 ]. NF1 is characterized by prominent skeletal manifestations caused by the loss of the NF1 gene[ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported differing incidence rates, but the frequency of the disease is 1/(2500-4000)[ 2 , 3 , 8 ]. NF1 is characterized by prominent skeletal manifestations caused by the loss of the NF1 gene[ 3 ]. About 10%-25% of NF-1 patients develop bone deformities, including scoliosis, congenital arch, pseudarthrosis, bone cysts, cortical bone thinning, and subperiosteal bone hyperplasia, seriously reducing the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%